KARAKTERISTIK ALAT TANGKAP DAN DISTRIBUSI DAERAH PENANGKAPAN GILLNET, HANDLINE, DAN PURSE SEINE DI PERAIRAN TELUK AMBON - Jacobus B. Paillin; Julian Tuhumury; Fernando G. Molle (Universitas Pattimura, 2025)
Fishing activities in Ambon Bay are potentially economic benefit due to the richness of its natural biodiversity and is supported by the oceanographic condition. This study aims to observe the characteristic of fishing gears and to map the distribution of fishing grounds of several fishing gears such as gillnets, handlines, trolled lines and purse seines in Ambon Bay. The study was conducted from April to June 2023. Data on the characteristics of each fishing gear were collected through interviews, while fishing grounds for each gear were obtained using Garmin 62s GPS and then mapped using a GIS application. The results showed there were two main types of gillnets, drift gillnets and bottom gillnets, which were operated at the southern and western coastal of Ambon Bay. Purse seines were operated at deeper waters occupying larger fishing grounds, while handlines and trolled lines were commonly used at the shallow waters of the eastern and southwestern parts. Technical characteristics of the gear, environmental conditions, and the availability of target fish influenced the distribution pattern of these fishing gear.